Hepatoprotective Activity of Methanolic Extract of Rhyncosia Beddomei Baker Leaves Against Carbon Tetrachloride Induced Hepatotoxicity - Ashoka Babu V.L, Arunachalam G, Jayaveera K.N, Madhavan.V, Shanaz Banu (Journal of Applied Pharmaceutical Science)
Rhyncosia beddomei Baker commonly known as Adavi-kandi, Vendiaku in Telugu belongs to the family Fabaceae.In the present study, the methanolic extract of Rhyncosia beddomei leaves was evaluated for its hepatoprotective effect against CCl4 induced hepatic injury in rats. Alteration in the levels of biochemical markers of hepatic damage like SGOT, SGPT, ALP, triglycerides, bilirubin, total proteins and liver weight were tested in both treated and untreated groups. CCl4 (1ml/kg) enhanced the SGPT, SGOT, ALP, triglycerides, liver weight and reduced total proteins significantly. Treatment with methanolic extract of Rhyncosia beddomei leaves (200mg/kg and 400mg/kg) has brought back the altered levels of altered levels of biochemical markers significantly to the near normal levels in the dose dependant manner. Histopathological studies supported the hepatoprotective activity of Rhyncosia beddomei Baker.
Keywords: Rhyncosia beddomei, Hepatoprotective activity, Biochemical markers, SGOT, SGPT, ALP